HUBUNGAN REWARD DENGAN KINERJA PERAWAT DI RUMAH SAKIT UMUM DAERAH TANJUNG PURA TAHUN 2017 - Juliati Juliati (Jurnal Keperawatan Priority, 2018)
Hospital service is a multi-disciplinary service and one part of the healthy service. That has a quality determinant contribution and forms the image of a hospital is a nurse. The performance of nurses is the appearance of the work of nurses in providing nursing services in the form of nursing care Awarding based on performance can have a positive impact on the behavior of nurses, causing job satisfaction for nurses, giving a positive impact on the ability of the hospital. Able to achieve the achievement of goals that have been designed and maintain more health workers who are able to work with high achievement.Research Objectives To determine the relationship between Reward and Performance at Tanjung Pura, Public Hospital Year 2017, the number of research samples 30 people. The results of statistical tests show that by using a significant level of 0.05 and then obtained statisticals test results show that there is a Reward Relationship with Performance Nurses can be seen from the significant value 0.000 <0.05. The result of hypothesis testing to see the relationship between variables X and variable Y is with significant level (α) = 5% (0,05) and df = 1 obtained result p.value = 0,000 at df = 1 where sig <α (0,000 <0 , 05) then it can be known there is a Reward Relationship with Performance Nurse at Tanjung Pura Public Hospital Year 2017.Reward given 18 respondents (60.0%) and minority of 12 respondents (40.0%), good performance 17 respondents (56.7%) and minority 13 respondents (43.3%), there is a significant relationship between Reward and Nurse Performance.It is expected to be the input for the hospital leader to give reward for the nurse so that the nurse can improve its performance on the achievement, it is expected to be the motivation for the nurse to keep improving his work performance, can be refrensi material, add the information and study the student literature especially regarding the reward system.